Dukungan Sosial dengan Kebermaknaan Hidup pada Pasien ODHA: Social Support with Meaning of Life in PLHIV patients - Arini Akmilatun Nisak; Liyanovitasari (Journal of Holistics and Health Sciences, 2024)
HIV/AIDS is a chronic disease, if this condition is experienced for a long period of time it can lead to thoughts of life being meaningless. The meaning of life is important for someone to understand the nature and purpose of life in the world. External factors that influence the meaning of life include material things, work and social support. Through the social support they receive, PLWHA feel part of society because they feel loved, appreciated and function in their social environment. Objective: To determine the relationship between social support and the meaning of life in PLWHA patients. Method: This research uses a correlational descriptive design with a cross sectional approach. The population of this study were all PLWHA outpatients at the Bergas Community Health Center with a total of 146 people. The sampling technique used was purposive sampling with a sample size of 107 respondents. The questionnaire for support was adapted from the Social Provision Scale developed by Cutrona & Rusel (1987) while the meaningfulness of life questionnaire was adapted from the Purpose in Life Scale (PIL-R) developed by Crumbaugh & Maholick (1964). Data analysis in this research used Spearman Rho. The research results showed that the majority of respondents received high category social support, 56 respondents (52.3%). Meanwhile, the meaning of life is also in the high category, as many as 57 respondents (53.3%). The group of respondents who received good social support tended to find the meaning of a good life 64% greater than the group of respondents with less social support. Conclusion: There is a relationship between social support and the meaning of life in PLWHA patients with a p value of 0.001 < 0.05 with an r value of 0.311 which shows the strength of the relationship in the medium category. Suggestion: PLWHA patients are expected to receive social support from the surrounding environment so they can find meaning in life.   ABSTRAK HIV/AIDS merupakan salah satu penyakit kronis, apabila kondisi tersebut dirasakan dalam jangka waktu lama dapat menimbulkan pemikiran hidup tidak bermakna. Kebermaknaan hidup penting bagi seseorang untuk memahami bagaimana hakikat dan tujuan hidup di dunia. Faktor eksternal yang mempengaruhi kebermaknaan hidup berupa material, pekerjaan dan dukungan sosial. Melalui dukungan sosial yang diterima, maka ODHA merasa menjadi bagian dari masyarakat karena merasa dicintai, perasaan dihargai dan berfungsi pada lingkungan sosialnya. Tujuan: Untuk mengetahui hubungan antara dukungan sosial dengan kebermaknaan hidup pada pasien ODHA. Metode: Penelitian ini menggunakan desain deskriptif korelasional dengan pendekatan cross sectional. Populasi penelitian ini seluruh pasien ODHA rawat jalan di Puskesmas Bergas dengan jumlah 146 orang. Teknik sampling yang digunakan adalah purposive sampling dengan jumlah sampel 107 responden. Kuesioner untuk dukungan diadaptasi dari Social Provision Scale yang dikembangkan oleh Cutrona & Rusel (1987) sedangkan kuesioner kebermaknaan hidup diadaptasi dari Purpose in Life Scale (PIL-R) yang dikembangkan oleh Crumbaugh & Maholick (1964). Analisis data pada penilitian ini menggunakan Spearman Rho. Hasil penelitian menunjukan bahwa mayoritas responden mendapatkan dukungan sosial kategori tinggi sebanyak 56 responden (52,3%). Sedangkan kebermaknaan hidup juga pada kategori tinggi sebanyak 57 responden (53,3%). Kelompok responden yang mendapat dukungan sosial baik cenderung mendpatkan kebermaknaan hidup baik sebesar 64% lebih besar dibandingkan dengan kelompok responden dengan dukungan social kurang. Kesimpulan: Ada hubungan antara dukungan sosial dengan kebermaknaan hidup pada pasien ODHA dengan p value 0,001 < 0,05 dengan nilai r 0,311 yang menunjukkan kekuatan hubungan dalam kategori sedang. Saran: Pasien ODHA diharapkan mendapatkan dukungan sosial dari lingkungan sekitar agar dapat menemukan kebermaknaan hidup dengan baik.